Lost in the Net? Broadband Internet and Youth Mental Health - Dante Donati; Ruben Durante; Francesco Sobbrio; Dijana Zejcirovic (CESifo GmbH, 2025)
How does the internet affect young people's mental health? We study this question using administrative data on the universe of cases of mental disorders diagnosed in Italian hospitals between 2001 and 2013, which we combine with broadband internet availability at the municipal level. Broadband internet access raises the prevalence of mental disorders among younger cohorts (born between 1985 and 1995) by 0.08 standard deviation units, but it does not impact older individuals (1974 and 1984). The adverse effects are driven by individuals who were exposed early in their lives (before the age of 20). These effects persist when examining instances of self-harm and urgent or compulsory hospitalizations, indicating that the negative outcomes are not merely a result of increased awareness and detection of these conditions. The detrimental impacts span across different pathologies, including depression, anxiety, drug abuse, and personality disorders for both genders, in addition to eating disorders for females.
Keywords: I12; I31; L82; L86; 330; mental health; internet; ADSL; 3G